1996
DOI: 10.1038/nm0396-347
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin and DRPLA proteins selectively interact with the enzyme GAPDH

Abstract: At least five adult-onset neurodegenerative diseases, including Huntingtin disease (HD), and dentatorubral-pallidoluysian atrophy (DRPLA) are produced by genes containing a variably increased CAG repeat within the coding region. The size range of the repeats is similar in all diseases; unaffected individuals have fewer than 30 CAG repeats, whereas affected patients usually have more than 40 repeats. The size of the inherited CAG repeat correlates with the severity and age of disease onset. The CAG triplet repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
227
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(232 citation statements)
references
References 28 publications
3
227
0
2
Order By: Relevance
“…GAPDH binds to glutamine repeats in Huntingtin and other polyglutaminecontaining proteins associated with neurodegenerative diseases (16,17). GAPDH also binds to amyloid precursor protein (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAPDH binds to glutamine repeats in Huntingtin and other polyglutaminecontaining proteins associated with neurodegenerative diseases (16,17). GAPDH also binds to amyloid precursor protein (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GAPDH can bind to Huntingtin, the protein whose glutamine repeats may mediate the symptoms of Huntington disease (HD) (16), as well as to the gene products with glutamine repeats involved in other neurodegenerative diseases such as spinocerebellar ataxia type-I (17), spinobulbar muscular atrophy (17), and dentatorubral pallidoluysian atrophy (16). Furthermore, GAPDH can bind to the cytoplasmic domain of amyloid precursor protein (18).…”
mentioning
confidence: 99%
“…Nevertheless, recent studies have suggested that abnormal interactions between the mutated huntingtin and other proteins could be involved in the pathogenesis of HD. Thus, huntingtin has been shown to interact with several proteins including a cytoplasmic protein that associates with microtubules, mitochondria, and synaptic vesicles (HAP-1; [45]), glyceraldehyde phosphate dehydrogenase (GAPDH; [46]), an unidentified calmodulin associated protein [47], an ubiquitin-associated protein (HIP-2; [48]), and a protein homologous to the yeast cytoskeleton-associated protein sla2p (HIP-1; [49]). …”
Section: Huntington's Diseasementioning
confidence: 99%
“…To date, a number of hypotheses regarding the molecular mechanisms of neurodegeneration caused by expansion of CAG repeats have been proposed, including position effect hypothesis, polar zipper theory, a hypothesis of the expanded polyglutamine tracts as a substrate for transglutaminase, and a hypothesis of neurotoxicity caused by the expanded polyglutamine tracts. Recently proteins which may interact with the polyglutamine tract were identified (HAP1 and GAPDH) (Li et al, 1995;Burke et al, 1996). Burke et al proposed that stronger binding of mutant DRPLAP carrying expanded polyglutamine tract with GAPDH than that of wild type DRPLAP may result in a decrease in GAPDH activity and energy failure in cells expressing mutant DRPLAP (Burke et al, 1996).…”
Section: Mechanisms Of Neurodegeneration Caused By Ca G Repeat Expansionmentioning
confidence: 99%
“…Recently proteins which may interact with the polyglutamine tract were identified (HAP1 and GAPDH) (Li et al, 1995;Burke et al, 1996). Burke et al proposed that stronger binding of mutant DRPLAP carrying expanded polyglutamine tract with GAPDH than that of wild type DRPLAP may result in a decrease in GAPDH activity and energy failure in cells expressing mutant DRPLAP (Burke et al, 1996).…”
Section: Mechanisms Of Neurodegeneration Caused By Ca G Repeat Expansionmentioning
confidence: 99%